Odpowiedzi

2010-01-17T16:21:12+01:00
Metoda podstawiania:
5=3x-y
5x-2y=7

y=-5+3x
5x-2(-5+3x)=7

y=-5+3x
5x+10-6x=7

y=-5+3x
x=3

y=-5+3*3
x=3

y=4
x=3

Metoda przeciwnych współczynników:
5=3x-y /*(-2)
5x-2y=7

-6x+2y=-10
5x-2y=7
------------
-x=-3
x=3

x=3
5=3*3-y

x=3
y=9-5

x=3
y=4
Najlepsza Odpowiedź!
2010-01-17T16:26:16+01:00
5=3x-y
5x-2y=7

#metoda przeciwnych współczynników:
5=3x-y
5x-2y=7

3x-y=5/×(-2)
5x-2y=7

-6x+2y=-10
5x-2y=7

-x=-3/×(-1)
x=3
9-y=5

x=3
-y=-4/×(-1)

x=3
x=4

#metoda podstawiania

5=3x-y
5x-2y=7

-y=5-3x /× (-1)
5x-2y=7

y=-5+3x
5x-2(-5+3x)=7

y=-5+3x
5x+10-6x=7

y=-5+3x
-x=-3 / × (-1)

y=-5+3x
x=3

y=-5 + 9
x=3

y=4
x=3